Faktor-Faktor Penyebab Kesulitan Belajar IPA dan Solusi Alternatifnya: Systematic Literature Review - Fahmi Yahya; Indah Dwi Lestari; Hermansyah Hermansyah; Eryuni Ramdhayani (Indonesian Journal of Applied Science and Technology, 2021)
Science (IPA) is a core subject at the primary and secondary education levels requiring comprehension of abstract concepts alongside scientific thinking skills. High rates of science learning difficulties are consistently reported internationally, including in Indonesia; however, no systematic synthesis has comprehensively summarised contributing factors and alternative solutions across all school levels (Elementary–High School) in a single manuscript. This review aims to identify factors causing science learning difficulties and effective alternative solutions based on the scientific literature from 2012 to 2021. Searches were conducted on Scopus, Web of Science, and ERIC databases following the PRISMA 2020 guidelines. Twenty-five articles meeting inclusion criteria were analysed through thematic narrative synthesis. Results show factors divide into internal (low interest and motivation, science anxiety, weak prerequisite knowledge) and external (teacher-centred pedagogy, inadequate laboratory facilities, insufficient parental support). Proven effective alternative solutions include inquiry-based learning, cooperative learning, technology/visual media use, and structured remedial programmes. Conclusion: science learning difficulties are multifactorial; consistent implementation of inquiry and cooperative approaches improves student engagement and achievement across educational levels.